Comparison of sub‐ versus suprafascially raised anterolateral thigh free flaps with regard to donor‐site morbidity, function and aesthetics. Issue 5 (20th November 2017) - Fischer, Sebastian; Diehm, Yannick; Hirche, Christoph; Kremer, Thomas; Daigeler, Adrien; Kneser, Ulrich; Hernekamp, J. Frederick
Abstract : Background: Although the anterolateral thigh flap (ALT) is one of the most frequently applied free flaps in plastic surgery, it remains controversial if the flap should be raised in a sub‐ or suprafascial plane. The purpose of this study was to compare both harvest techniques regarding donor‐site morbidity and outcomes. Methods: We included 40 pair‐matched patients, of whom 20 received a fasciocutaneous and 20 an adipocutaneous ALT free flap for extremity reconstruction. Patients were matched for age (±5 years), sex and affected extremity. Chart review focused on co‐morbidities, flap dimensions, course of perforator(s), postoperative complications, and surgery time. Follow‐up included sensation, range of motion, and muscle strength at the donor‐site. In addition, patients rated the aesthetic and functional outcome on a scale from 1 to 6 and completed a Quality of Life 36‐item Short‐Form Health Survey (SF‐36) as well as the lower extremity functional scale (LEFS) questionnaire. Results: Chart review did not reveal any significant differences among study groups. Follow‐up indicated better sensory outcomes after subfascial flap elevation, but without statistical significance. Range of motion and muscle strength were not impaired in any patient. Neither patients' ratings regarding aesthetic and functional outcomes nor scores of the SF‐36 or LEFS differed significantly among study groups. Conclusion: Sub‐ or suprafascial harvest of the ALT free flap for extremity reconstruction does not impact donor‐site morbidity or complications.